2019
DOI: 10.3390/ijerph16050736
|View full text |Cite
|
Sign up to set email alerts
|

Propagating Change: Using RE-FRAME to Scale and Sustain A Community-Based Childhood Obesity Prevention Initiative

Abstract: Sustainable Childhood Obesity Prevention through Community Engagement (SCOPE) has developed Live 5-2-1-0, a multi-sectoral, multi-component community-based childhood obesity prevention initiative grounded in systems thinking and participatory research principles. Building on previous work, this study continued implementation of an innovative knowledge exchange model, RE-FRAME, in two ‘new’ and two ‘existing’ Live 5-2-1-0 communities. This mixed-methods study examined follow-up data to determine the nature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 26 publications
0
46
0
2
Order By: Relevance
“…10 Health disparities research has shown that individual-level strategies may not be efficacious within vulnerable communities where there is a clear need to leverage social and familial connectedness for health promotion and disease prevention. 45 In fact, the most effective strategies for vulnerable, minority populations recognize that health behaviors occur in the context of relationships with family and friends. 46 Thus, interventions grounded in the SCT may need to be adapted to account for social and familial factors in order to maximize intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…10 Health disparities research has shown that individual-level strategies may not be efficacious within vulnerable communities where there is a clear need to leverage social and familial connectedness for health promotion and disease prevention. 45 In fact, the most effective strategies for vulnerable, minority populations recognize that health behaviors occur in the context of relationships with family and friends. 46 Thus, interventions grounded in the SCT may need to be adapted to account for social and familial factors in order to maximize intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Websites and frequent meetings were also recommended (Heo et al., 2018 ). Others recommended transparent agendas, budgets and role definitions (van Duijn et al., 2018 ; Eckart et al., 2019 ; Green et al., 2014 ; Hedberg et al., 2019 ; Ho et al., 2019 ; Kennedy et al., 2019 ; Walker et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps most importantly, financing often comes with restrictions (Fisher & Elnitsky, 2012 ). In some cases, cuts in funding brought focus to collaboratives (Kennedy et al., 2019 ; Zahner et al., 2014 ) or were themselves a catalyst for collaboration (Cantor et al., 2015a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jedoch können laut einer Studie 70 % der Veränderungsprojekte in Krankenhäusern nicht nachhaltig implementiert werden. Die größte Herausforderung liegt nicht im Start eines Verbesserungsprojektes, sondern in der Weiterführung der Veränderungsprozesse,nachdemderersteEnthusiasmusverflogenist [19].Für eine nachhaltige Prozessverbesserung bedarf es daher Beständigkeit, Akzeptanz und Zusammenführung [20].…”
Section: Erfolgsfaktoren Nachhaltiger Prozessverbesserungenunclassified